Hubungan Kegagalan Tata Kelola dan Pelanggaran Etika Bisnis terhadap Reputasi Kinerja Keuangan & Non-Keuangan Perusahaan: Studi Kasus PT Shell - Moch Herdin Batistuta Akbar; Octavianunisa, Widuri; Hakim, Adi Lukman (MANABIS: Jurnal Manajemen dan Bisnis, 2025)
This study aims to analyze the impact of business ethics violations on the reputation and performance of PT Shell, by identifying the forms of violations that occur and the mechanism of their impact on the company's financial and non-financial aspects. The research uses a qualitative approach with a case study design. Data was collected through documentation studies of annual reports, media coverage, government institution reports, as well as in-depth interviews with key informants consisting of former PT Shell officials, energy market analysts, and senior journalists. Data were analyzed using thematic analysis techniques. The results reveal that PT Shell faced various business ethics violations, primarily in the areas of corporate governance (corruption), operational safety (fires and oil spills), and community relations (social and environmental conflicts). These violations functioned as negative signals that significantly damaged the company's reputation, reflected in declining trust from the public, investors, and other stakeholders. The impact on company performance was complex, including direct financial losses (fines, cleanup costs) and indirect losses (project delays, increased cost of capital), as well as non-financial losses such as decreased employee morale, worsened relations with regulators, and increased resistance from communities. It is concluded that there is a strong causal relationship between business ethics violations, reputation decline, and performance decline of PT Shell. This research confirms that ethical integrity and the strong implementation of Good Corporate Governance are not a cost burden, but rather a strategic asset and critical investment for protecting reputation and ensuring sustainable company performance.